Pengaruh Gerakan Boikot Terkait Konflik Israel-Palestina Terhadap Profitabilitas Perusahaan Food and Beverages (F&B) yang terdaftar di Bursa Efek Indonesia (BEI) Periode Tahun 2021-2024 - Fadillah, Lida; Nugraheni, Krisnawati Setyaningrum (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The renewed escalation of the Israel–Palestine conflict in late 2023 has led to the emergence of boycott movements against products from companies suspected of being affiliated with Israel. One of the affected sectors is the Food and Beverages (F&B) industry, which plays a key role in meeting the population’s primary needs. This study aims to analyze the effect of product boycott movements on the profitability of F&B companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Profitability is measured using financial ratios such as Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The study applies a quantitative method with a causal approach, using secondary data obtained from annual financial reports published on the IDX website. Historical data are taken from the 2021–2022 period as the pre-boycott years and from 2023–2024 as the post-boycott years. The results indicate that the boycott movement has a negative but statistically insignificant impact on company profitability. This study is expected to serve as a reference for the public and industry stakeholders in understanding the economic impact of boycott movements. Future research is recommended to apply different analytical methods to produce more comprehensive and in-depth results.
Keywords: Product Boycott; Profitability; F&B Companies